Epidemiology of Alcohol Poisoning and Its Outcome in the North-West of Iran - Morteza Bagi, Hamid Reza; Tagizadieh, Mohammad; Moharamzadeh, Payman; Pouraghaei, Mahboob; Kahvareh Barhagi, Aynaz; Shahsavari Nia, kavous (Archives of Academic Emergency Medicine, 2018)
Introduction: Alcohol poisoning is one of the main preventable causes of death, disability, and injury in many societies. Ethanol and methanol are the most prevalent kinds of alcohol used. There is no any exact reports of alcohol poisoning and its outcome in Iranian society. Therefore, the present study was assessed the status of alcohol poisoning and its outcome in referees to the emergency department. Methods: This is a cross-sectional study which was done from July 2013 to 2014 in Sina Trauma Center, Tabriz, Iran. The studied population included all alcohol poisoning cases referred to this center. Demographic variables, clinical evaluation, laboratory tests, and patient's outcome were evaluated. To assess the relation between evaluated factors and outcome of alcohol poisoning. After univariate analysis a multivariate logistic regression was applied to evaluate independent risk factors for death. P<0.05 was considered as a significant level. Results: Lastly 81 patients with alcohol poisoning were entered to the study (91.4% male) with the mean age of 27.9±10.4 years. Ten (12.3%) subjects were dialyzed and 34 (42%) cases hospitalized that 3 (3.7%) of them died. The multivariate logistic regression test displayed that plasma creatinine level (OR=2.2 95%Cl: 1.8-2.5; p=0.015) and need for dialysis (OR=6.4; 95%Cl: 5.3-7.5; p<0.001) were the only risk factors of death among these patients. Conclusion: The findings of the present study revealed that total mortality rate of referees to the emergency with alcohol poisoning was 3.7% all of whom related to methanol poisoning. Based on this result, the mortality rate of methanol poisoning was estimated 20%. Need for dialysis and increasing the creatinine level were accounted as independent risk factors of death.